Adaptogenic potential of andrographolide: An active principle of the king of bitters (Andrographis paniculata) - Thakur, Ajit Kumar (J Tradit Complement Med, 2014)
Andrographolide is a major bioactive secondary plant metabolite isolated Andrographis paniculata (Burm. F.) Wall. Ex. Nees. (穿心蓮 chuān xīn lián), a well-known traditionally used medicinal herb. The aim of the study was to pharmacologically evaluate the beneficial effect of andrographolide on stress-induced thermoregulatory and other physiological responses in mice. A stress-induced hyperthermia test was conducted in mice. The test agents were orally administered once daily for 11 consecutive days, and treatment effects on body weight changes, basal rectal temperature, and foot-shock-triggered hyperthermic responses were quantified on Day 1, Day 5, Day 7, and Day 10 of the experiments. Pentobarbital-induced hypnosis was quantified on the 11(th) day of treatment. Observations made during a pilot dose finding experiment revealed that, like A. paniculata extracts, pure andrographolide also possess adaptogenic properties. Observed dose-dependent efficacies of 3 mg/kg/d, 10 mg/kg/d, and 30 mg/kg/d andrographolide in the pilot experiment were reconfirmed by conducting two further analogous experiments using separate groups of either male or female mice. In these confirmatory experiments, efficacies of andrographolide were compared with that of 5 mg/kg/d oral doses of the standard anxiolytic diazepam. Significantly reduced body weights and elevated core temperatures of the three vehicle-treated control groups observed on the 5(th) day and subsequent observational days were completely absent even in the groups treated with the lowest andrographolide dose (3 mg/kg/d) or diazepam (5 mg/kg/d). Benzodiazepine-like potentiation of pentobarbital hypnosis was observed in andrographolide-treated animals. These observations reveal that andrographolide is functionally a diazepam-like desensitizer of biological mechanisms, and processes involved in stress trigger thermoregulatory and other physiological responses.